Neotyping of three species of the genus Bletia (Orchidaceae) - Sosa, Victoria (Instituto de Ecología, A.C., 1992)
Neotypes for three species of Bletia (Orchidaceae) described by Lexarza: B. campanulata, B. coccinea and B. punctata are here designated. Their main diagnostic morphological characters are discussed based on herbarium and living material.